Automated Number Plate Recognition Using Template Matching - Aggarwal, Nancy; Sethi, Shilpa (International Journal of Computer Sciences and Engineering, 2018)
Automated number plate recognition is an image processing technique that uses number plate for identification and authorization of products. The paper aims to design a vehicle identification system by using template matching. The proposed system detects an authorized vehicle followed by capturing its image. The system is highly efficient and can be installed in high security zone like government offices including parliament and Supreme Court. The system is implemented in MAT lab. The experimental result of proposed system is also compared with existing pattern matching technique.